Chronic kidney diseases and inflammation research: a bibliometric analysis - Wang, Heyong; Chen, Yang; Gou, Yujuan; Yang, Dianxing; Xiong, Lanyue (Frontiers in Medicine, 2024)
Background：Chronic kidney diseases (CKD) is a severe public health problem. This study aimed to explore the field of inflammation-related research in CKD from a bibliometric perspective.Methods: Relevant literature published between 2004 and 2023 were searched from the Web of Science database. The bibliometric analysis were performed to summarize countries, institutions, authors, journals and keywords using VOSviewer and CiteSpace.Results: A total of 9,287 publications on CKD and inflammation were included.